2021
DOI: 10.1039/d0sm01662d
|View full text |Cite
|
Sign up to set email alerts
|

Magttice: a lattice model for hard-magnetic soft materials

Abstract: Magnetic actuation has emerged as a powerful and versatile mechanism for diverse applications, ranging from soft robotics, biomedical devices to functional metamaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…Subsequently, Garcia-Gonzalez [ 45 ] developed a continuum framework for modeling the effect of viscoelasticity on the magneto-mechanical response of hard-magnetic soft materials under dynamic and static loading conditions. Further, Ye et al [ 46 ] developed a computationally efficient numerical model for hard-magnetic soft materials by decomposing the elastic deformation energy into lattice volumetric changes and stretching. Chen et al [ 47 ] reported a theoretical model for characterizing the complex transformations of planar hard-magnetic soft beams.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Garcia-Gonzalez [ 45 ] developed a continuum framework for modeling the effect of viscoelasticity on the magneto-mechanical response of hard-magnetic soft materials under dynamic and static loading conditions. Further, Ye et al [ 46 ] developed a computationally efficient numerical model for hard-magnetic soft materials by decomposing the elastic deformation energy into lattice volumetric changes and stretching. Chen et al [ 47 ] reported a theoretical model for characterizing the complex transformations of planar hard-magnetic soft beams.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical modeling of HMSMs has been the subject of a plethora of research articles in recent years (e.g., [23][24][25][26][27][28][29][30][31][32]). In particular, Zhao et al [24] developed a continuum formulation with an asymmetric Cauchy stress tensor, which is very similar to the classical continuum theory in the sense that it neither needs non-classical material parameters nor additional degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…Micromechanical and lattice models for the deformation analysis of HMSMs have been also formulated by Zhang et al [28], Garcia-Gonzalez and Hossain [29,30], and Ye et at. [31]. From a different point of view, Dadgar-Rad and Hossain [32] focused on the well-known phenomenon that the interaction between remnant and external magnetic fluxes induces a body couple on the continuum body (e.g., [40]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this microstructural modelling has also been approached by molecular dynamics simulations [44]. Another interesting approach is due to Ye et al [51]. In this work, the authors developed a computational framework, called "Magttice", to model hMAPs with the combinations of FE scheme and lattice models.…”
Section: Introductionmentioning
confidence: 99%